Predictive features of ligand‐specific signaling through the estrogen receptor. Issue 4 (23rd April 2016) - Nwachukwu, Jerome C; Srinivasan, Sathish; Zheng, Yangfan; Wang, Song; Min, Jian; Dong, Chune; Liao, Zongquan; Nowak, Jason; Wright, Nicholas J; Houtman, René; Carlson, Kathryn E; Josan, Jatinder S; et al.
Abstract: Some estrogen receptor‐α (ERα)‐targeted breast cancer therapies such as tamoxifen have tissue‐selective or cell‐specific activities, while others have similar activities in different cell types. To identify biophysical determinants of cell‐specific signaling and breast cancer cell proliferation, we synthesized 241 ERα ligands based on 19 chemical scaffolds, and compared ligand response using quantitative bioassays for canonical ERα activities and X‐ray crystallography. Ligands that regulate the dynamics and stability of the coactivator‐binding site in the C‐terminal ligand‐binding domain, called activation function‐2 (AF‐2), showed similar activity profiles in different cell types. Such ligands induced breast cancer cell proliferation in a manner that was predicted by the canonical recruitment of the coactivators NCOA1/2/3 and induction of the GREB1 proliferative gene. For some ligand series, a single inter‐atomic distance in the ligand‐binding domain predicted their proliferative effects. In contrast, the N‐terminal coactivator‐binding site, activation function‐1 (AF‐1), determined cell‐specific signaling induced by ligands that used alternate mechanisms to control cell proliferation. Thus, incorporating systems structural analyses with quantitative chemical biology reveals how ligands can achieve distinct allosteric signaling outcomes through ERα. Synopsis: Chemical biology profiling and X‐ray crystallography reveal specific structural perturbations that define how different types of ERα ligands use alternate signaling pathways to regulate proliferation of ERα + breast cancer cells. Ligands that regulate the percent of time ERα is in the active conformation drive transcriptional activity and cell proliferation through the canonical ERα signaling pathway, where recruitment of NCOA1/2/3 coactivators drives GREB1 expression and the proliferation of ERα + breast cancer cells. Cell‐specific signaling through ERα is associated with an alternate causality model of ligand response, where NCOA1/2/3 recruitment and GREB1 expression do not determine the proliferative effect on ERα + breast cancer cells. Ligands that drive cell‐specific signaling through ERα without a prototypical SERM side chain change the shape of the coactivator‐binding site and alter the coactivator‐binding preferences of the ERα ligand‐binding domain. Inter‐atomic distances in crystal structures of the ERα ligand‐binding domain can predict the proliferative effects of some ligand series. Abstract : Chemical biology profiling and X‐ray crystallography reveal specific structural perturbations that define how different types of ERα ligands use alternate signaling pathways to regulate proliferation of ERα + breast cancer cells.